Are positive and negative outcomes of organizational justice conditioned by leader-member exchange? - Or Shkoler; Aharon Tziner; Cristinel Vasiliu; Claudiu-Nicolae Ghinea (Amfiteatru Economic Journal, 2021)
The workplace is complex, comprising many entities (abstract and tangible) - affective states, attitudes, and perceptions, but also workers and managers themselves and their behaviors. Understanding the link between them is vital for organizational prosperity. In the current paper, the perceptions of organizational justice are investigated as a precursor to two important outcomes - organizational citizenship behavior and counterproductive work behavior. To that end, a two-step research study was conducted to test a moderatedmediation model. First, a pilot study of 93 Romanian employees was undertaken, followed by a larger study consisting of 3293 Romanian workers. There were distinct differences between the two studies. Implications, limitations, and suggestions for future research are discussed.
Keywords: D23; M54; O15; 330; counterproductive work behavior (CWB); leader-member exchange (LMX); moderated-mediation; organizational citizenship behavior (OCB); organizational justice; work motivation